Only eye study 3 (OnES 3): a qualitative study into how surgeons approach surgery in patients with only one seeing eye - Peter Shah; Lee Jones; Jonathan P Whyte; Graham Lee (BMJ Open)
Objective Performing surgery on an ‘only eye’ patient is considered high stakes. The purpose of this study is to explore the process of only eye surgery from the perspective of ophthalmic surgeons and improve both patient and surgeon experience.Design, setting and participants A cohort of 76 Australian consultant ophthalmologists, divided into three focus groups, were recruited via online webinar to participate in a guided focus group discussion about only eye surgery. Qualitative data regarding participant experience of performing only eye surgery were collected in audio and text form. Thematic analysis was conducted to identify patterns in the data.Main outcome measure Identification of themes relevant to only eye surgery.Results Five overarching themes relevant to only eye surgery were identified: (1) differences in the surgical decision-making process; (2) differences in the approach to consent, (3) implementation of additional risk reduction strategies, (4) value of having colleagues to discuss and plan surgery with and (5) psychological challenges. A divergent theme was identified: (6) that all surgery, only eye or not, should be treated the same.Conclusions This study identifies challenges associated with clinical management of only eye patients across their surgical journey. A conceptual framework to guide surgeons when managing only eye patients is provided which has potential to promote a more unified approach to treating this high-stakes cohort.